Z/E‐Isomerism of 3‐[4‐(dimethylamino)phenyl]‐2‐(2, 4, 6‐tribromophenyl)acrylonitrile: crystal structures and secondary intermolecular interactions. Issue 1 (18th December 2017) - Tammisetti, Renuka Devi; Kosilkin, Ilya V.; Guzei, Ilia A.; Khrustalev, Victor N.; Dalton, Larry; Timofeeva, Tatiana V.
Abstract : The crystal structures of the energetically similar Z and E isomers of 3‐[4‐(dimethylamino)phenyl]‐2‐(2, 4, 6‐tribromophenyl)acrylonitrile differ in the nature of their strong intermolecular nonbonding interactions, which are Br…N in the case of the Z isomer and Br…Br for the E isomer. Abstract : The Z and E isomers of 3‐[4‐(dimethylamino)phenyl]‐2‐(2, 4, 6‐tribromophenyl)acrylonitrile, C17 H13 Br3 N2, (1 ), were obtained simultaneously by a Knoevenagel condensation between 4‐(dimethylamino)benzaldehyde and 2‐(2, 4, 6‐tribromophenyl)acetonitrile, and were investigated by X‐ray diffraction and density functional theory (DFT) quantum‐chemical calculations. The ( Z )‐(1 ) isomer is monoclinic (space group P 21 / n, Z ′ = 1), whereas the ( E )‐(1 ) isomer is triclinic (space group P, Z ′ = 2). The two crystallographically‐independent molecules of ( E )‐(1 ) adopt similar geometries. The corresponding bond lengths and angles in the two isomers of (1 ) are very similar. The difference in the calculated total energies of isolated molecules of ( Z )‐(1 ) and ( E )‐(1 ) with DFT‐optimized geometries is ∼4.47 kJ mol −1, with the minimum value corresponding to the Z isomer. The crystal structure of ( Z )‐(1 ) reveals strong intermolecular nonvalent Br…N [3.100 (2) and 3.216 (3) Å] interactions which link the molecules into layers parallel to (10 ). In contrast, molecules of ( E )‐(1 ) in the crystal are bound to each other by strong nonvalent Br…Br [3.5556 (10) Å] and weak Br…N [3.433 (4) Å] interactions, forming chains propagating along [110]. The crystal packing of ( Z )‐(1 ) is denser than that of ( E )‐(1 ), implying that the crystal structure realized for ( Z )‐(1 ) is more stable than that for ( E )‐(1 ).